2011
DOI: 10.1038/emboj.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myosin light chain kinase regulates skeletal myogenesis by phosphorylation of MEF2C

Abstract: The MEF2 factors regulate transcription during cardiac and skeletal myogenesis. MEF2 factors establish skeletal muscle commitment by amplifying and synergizing with MyoD. While phosphorylation is known to regulate MEF2 function, lineage-specific regulation is unknown. Here, we show that phosphorylation of MEF2C on T 80 by skeletal myosin light chain kinase (skMLCK) enhances skeletal and not cardiac myogenesis. A phosphorylation-deficient MEF2C mutant (MEFT80A) enhanced cardiac, but not skeletal myogenesis in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 76 publications
3
54
0
Order By: Relevance
“…Both exendin-4 and EGF direct the DE differentiation toward primitive gut tube endoderm, and enhance proinsulin biosynthesis and expansion of pancreatic progenitor at later stages of hESC and hiPSC differentiation [18]. Recently, Nekoei et al [73] reported the generation of insulin-producing cells from WJ-MSC cultured in a serum-dependent differentiation containing exendin-4 [24], yet the efficiency of insulin induction was relatively low most likely due to absence of the stepwise differentiation process. Similarly, Kadam et al [74] reported a low yield of pancreatic β-cell-like clusters generated from monolayer cultures of placenta-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both exendin-4 and EGF direct the DE differentiation toward primitive gut tube endoderm, and enhance proinsulin biosynthesis and expansion of pancreatic progenitor at later stages of hESC and hiPSC differentiation [18]. Recently, Nekoei et al [73] reported the generation of insulin-producing cells from WJ-MSC cultured in a serum-dependent differentiation containing exendin-4 [24], yet the efficiency of insulin induction was relatively low most likely due to absence of the stepwise differentiation process. Similarly, Kadam et al [74] reported a low yield of pancreatic β-cell-like clusters generated from monolayer cultures of placenta-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, WJ-MSCs generated stable spheroidal bodies upon culturing in AggreWell plates, which showed an improved differentiation capacity into DE lineage. In both ESCs and iPSCs this technique has been proven to efficiently mediate the differentiation toward different developmental lineages [8, 24, 25], but it has not been tested in WJ-MSCs. Notably, differentiating WJ-MSCs in monolayer cultures toward insulin-producing cells resulted in the generation of cell aggregates; while remaining attached to the plate surface, cells within the cluster-like morphology showed a significant differentiation property [73, 76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyocyte formation (EB formation): Cardiomyocyte formation was induced by growing the mES cells in suspension culture conditions, in the absence of LIF, to form embryoid bodies (EBs), as described previously (Kennedy et al 2009;Al Madhoun et al 2011). Cells growing in monolayer (termed day 0) were brought into single cell suspension by treating for 5 min with 1× trypsin-EDTA (Invitrogen), and re-suspending in complete media, without LIF.…”
Section: Methodsmentioning
confidence: 99%
“…A member of the MADS box transcription factor regulator family, MEF2 is a protein found in developing skeletal muscle myotubes and of which there are four members: MEF2A, MEF2B, MEF2C, and MEF2D (Potthoff et al, 2007;Angelelli et al, 2008;Al Madhoun et al, 2011). The DNA-binding site of MEF2 is a segment of the conservative DNA sequence CTA(A/T) 4 TAG, which exists widely in the regulatory region of muscle tissue-specific expression genes, such as that for muscle creatine kinase (MCK) (Black and Olson, 1998).…”
mentioning
confidence: 99%